Viability and arbitrage under Knightian Uncertainty - M. Burzoni; F. Riedel; H. M. Soner (Bielefeld University, Center for Mathematical Economics (IMW), 2017)
We reconsider the microeconomic foundations of financial economics under Knightian Uncertainty. In a general framework, we discuss the absence of arbitrage, its relation to economic viability, and the existence of suitable nonlinear pricing expectations. Classical financial markets under risk and no ambiguity are contained as special cases, including various forms of the Efficient Market Hypothesis. For Knightian uncertainty, our approach unifies recent versions of the Fundamental Theorem of Asset Pricing under a common framework.
urn:nbn:de:0070-pub-29129630
Keywords: D53; G10; 330; robust finance; no arbitrage; viability; Knightian Uncertainty